Local growth of CuInSe2 micro solar cells for concentrator application. (December 2017) - Heidmann, Berit; Ringleb, Franziska; Eylers, Katharina; Levcenco, Sergiu; Bonse, Jörn; Andree, Stefan; Krüger, Jörg; Unold, Thomas; Boeck, Torsten; Lux-Steiner, Martha Ch.; Schmid, Martina
Abstract: A procedure to fabricate CuInSe2 (CISe) micro-absorbers and solar cells for concentrator applications is presented. The micro-absorbers are developed from indium precursor islands, which are deposited on a molybdenum coated glass substrate (back contact), followed by deposition of copper on top and subsequent selenization as well as selective etching of copper selenides. In order to compare the properties of the locally grown absorbers to those of conventional large area CISe films, we systematically examine the compositional and morphological homogeneity of the micro absorbers and carry out photoluminescence measurements. Preliminary devices for micro-concentrator solar cell applications are fabricated by optimizing the copper to indium ratio and the size of the indium precursor islands. The resulting micro solar cells provide a characteristic I–V curve under standard illumination conditions (1 sun). Highlights: A new bottom-up strategy for manufacturing CISe micro-absorbers is demonstrated. Optimized micro-absorbers offer the same quality as planar reference absorbers. Working micro solar cells were successfully fabricated. The efficiency can be increased under concentrated light illumination.